Cardiovascular Paediatric Medicines Development: Have Paediatric Investigation Plans Lost Heart? - Bethany Faulkner; M. Begoña Delgado-Charro (MDPI AG, 2020)
This work aimed to establish whether paediatric needs in cardiovascular diseases have been met by paediatric investigation plans (PIPs) produced since the development of the European Union Paediatric Regulation in 2007. The European Medicines Agency repository was searched for patterns in the development of paediatric medicines in general. Next, positive PIPs related to cardiovascular diseases were scrutinized for outcomes and compared to specific paediatric cardiovascular needs. In total, 1866 PIPs were identified with 12% corresponding to decisions taken for cardiovascular medicines. However, despite this therapeutic area having the greatest number of overall PIPs, only 14% of established needs in paediatric cardiovascular diseases were addressed by PIPs with positive decisions. Further, 71.9% of PIPs with decisions in cardiovascular disease corresponded to full waivers, so the product would not be studied in paediatrics. Despite the progress found in overall numbers of PIPs published, cardiovascular products are still commonly used off-label in paediatrics. Particularly, there is a need to develop products to treat heart failure and hypertension, two areas with clear unmet clinical needs in paediatrics. A case study on valsartan showed that industry, regulators, health technology assessment bodies, and prescribers should work together to reduce off-label use of paediatric cardiovascular diseases (CVD).